Biological soil crust recovery after long-term grazing exclusion in the Monte Desert (Argentina): Changes in coverage, spatial distribution, and soil nitrogen - Gómez, Diana A. (2012)
Disturbance by domestic grazing is recognized as the most widespread stressor of biological soil crust (BSC) communities. To assess the recovery of the BSC after grazing exclusion, we estimated the composition, cover, and spatial distribution of biological soil crusts, and their influence on soil nitrogen in a protected area after 40 years of grazing exclusion (Reserve MaB of Ñacuñán), and in its surrounding grazed matrix in the central Monte Desert. We considered two spatial scales: at the landscape scale we estimated vegetation and BSC cover in paired grazed and ungrazed sites of Larrea shrublands; at the microsite scale we assessed the influence of the dominant vascular plant, Larrea cuneifolia, on crust cover, and the influence of crust cover on soil nitrogen concentration. Grazing has a negative impact on soil crusts, which only develop under the protection of vascular plants in grazing areas. Grazing exclusion favors crust recovery, allowing black, lichen dominated crusts to develop in exposed areas between shrub canopies. The cover of the moss-dominated crusts was not significantly different at any of the two spatial scales analyzed. Soil nitrogen was higher in areas under L. cuneifolia and without BSC cover, suggesting that litterfall inputs currently exceed those from soil crust N2 fixation, perhaps because crust function has not yet recovered.